Imagery in cognitive behavioral supervision - Prasko, Jan; Dicevicius, Darius; Ociskova, Marie; Krone, Ilona; Slepecky, Milos; Albertina, Marija; Bagdonaviciene, Lina; Juskiene, Alicja (Neuro endocrinology letters, 2020)
OBJECTIVE: This article describes the role of imagery in supervision which is a part of the work of both the supervisee and the supervisor. Imagination bears outstanding importance in psychotherapy and supervision. METHOD: The relevant texts for this narrative review were identified through the Web of Science and PubMed databases, within the period 1990-2019. The search terms included: Supervision, Cognitive behavioural therapy, Imagination, Imagery, Imagery rescripting, Therapeutic relationship, Supervisory relationship. The report also includes information from the books referred to by the articles. The supervisory experiences of the authors were also incorporated. The theoretical part is supplemented with case vignettes of strategies using imagination in CBT supervision. RESULTS: Working with imagery can be used in transformative experiential learning. It can help to better map the situation with the patient, including its emotional components and basic psychological needs, to realise how the therapeutic relationship is set up, as well as to rework own therapist attitudes, schemas and emotional - behavioural responses, and plan future steps in the therapy. Many therapy steps could be learned during imagery exercises. Imagery also helps to understand and regulate the supervisory relationship. CONCLUSION: It is useful to integrate imagery to the supervision. Using imagery can help to understand the patient, the therapeutic relationship better, and to plan optimal therapeutic strategies, as well as reflect/self-reflect and train difficult skills which promote professional and personal growth.
Keywords: Attitude of Health Personnel; imaginace; Humans; postoj zdravotnického personálu; Imagery, Psychotherapy; Physician-Patient Relations; Cognitive Behavioral Therapy; imaginativní postupy v psychoterapii; lidé; vztahy mezi lékařem a pacientem; kognitivně behaviorální terapie; Imagination